Porcine gastric mucin (PGM) at the water/poly(dimethylsiloxane) (PDMS) interface influence of pH and ionic strength on its conformation, adsorption, and aqueous lubrication properties - Lee, Seunghwan (Langmuir : the ACS journal of surfaces and colloids, 2005)
We have investigated the influence of pH and ionic strength on the conformation of porcine gastric mucin (PGM) in bulk aqueous solution, its adsorption behavior onto poly(dimethylsiloxane) (PDMS) surfaces, and its lubricating behavior upon the self-mated sliding contact of a PDMS tribopair by means of circular dichroism (CD) spectroscopy, optical waveguide lightmode spectroscopy (OWLS), and pin-on-disk tribometry, respectively. In a low-concentration regime (1 mg/mL), where the formation of a mucus-gel is generally excluded, PGM is still observed to exhibit effective aqueous lubricating properties under specific conditions of acidic pH and low ionic strength. This behavior was closely correlated with specific conformations in the bulk solution as well as specific adsorption behavior at the water/PDMS interface. The lubrication mechanism of the self-mated sliding contact of PDMS by means of surface modification with PGM is discussed in terms of isoviscous-elastic/soft-elastohydrodynamic lubrication (soft-EHL)